Analysis of the Calculation of the Cost of Goods Produced Using the Full Costing Method - B*, Indayani; Qamariah, Nur (Universitas Syiah Kuala, 2023)
The calculation of the price of the product is a very important thing in determining the selling price of a product. The purpose of this research is to find out how to calculate the price of the product by using the full costing method and to analyze the comparison of the calculation of the prices of the products using the whole costing method with the calculations of the production price of nylon. The results of the research showed that the result of calculating the price for the product using the method of full costing is greater, that is, of Rs 194,000, while the calculation of the cost of production applied to Nillon's manufacturing products obtained Rs 193,000. From these calculations, there was a difference in the calculated price of production products, with a difference of Rs 1,000. This is because, for the time being, NILON has not calculated and grouped the overhead costs issued during the production process. The Nylon Wire Management Board should calculate all overhead costs in detail, whether they are variable or fixed. By carrying out calculations using the Full Costing Method, SMEs can calculate the price of production items more accurately by taking into account the entire component of production costs.